A resiliência do broadcast: o globoplay e as tensões jurídicas na constituição do streaming no Brasil - Souza, Wesley Wadim Passos Ferreira de (Universidade do Vale do Rio dos Sinos, 2021)
In this research we intend to explore one of the dimensions that compose the ambience that allowed the advancement of the streaming services in Brazil, taking as object the platform of Rede Globo de TV, Globoplay. After raising aspects of the socio-technical, normative and decision-making dimensions that compose the previous ambience, we call the concept of convergence of which we highlight the idea of normative convergence as an element of analysis. To this end, we used the archaeological target referenced in Foucault (2012) and Manovich (2002) and the methodological strategy of the frames and framing of Kilpp (2003). Globoplay as one of the elements that consubstantiated the resilience strategies of Globo presents itself as a fruitful object of observation, since through its interface with the user can perceive traces of this scenario in which one side has a model of production and distribution of audiovisual subject to very consolidated and limiting standards, with extremely reduced maneuvering margins (broadcast and segmented TV) and another an ambience that allows the constitution of something new, less submited to the frames regulations, where existing risks allow for greater gains. The research also allowed us to examine whether the new possibilities have already become new things.
Keywords: Streaming; Regulação; Convergência normativa; Ecossistema audiovisual; Regulation; Legal convergence; Audiovisual ecosystem; ACCNPQ::Ciências Sociais Aplicadas::Comunicação